2022
DOI: 10.3389/fonc.2022.863682
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Human GBM From Non-GBM Brain Tissue With Polarization Imaging Technique

Abstract: As for optical techniques, it is difficult for the 5-aminolevulinic (5-ALA) fluorescence guidance technique to completely detect glioma due to residual cells in the blind area and the dead angle of vision under microscopy. The purpose of this research is to characterize different microstructural information and optical properties of formalin-soaked unstained glioblastoma (GBM) and non-GBM tissue with the polarization imaging technique (PIT), and provide a novel method to detect GBM during surgery. In this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…It is based on the analysis of the modification of the polarization state of incident polarized light due to the interaction with the sample to be examined, which can be described by the Mueller matrix. In our previous work, it was confirmed that PIT can investigate optical information and microstructures of glioma and non-glioma tissues from clinical treatment based on backward scattering 3 × 3 Mueller matrix polarization imaging experimental setup, and the polarization properties of the glioma and non-glioma brain tissues have been characterized and reported ( Liu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 72%
“…It is based on the analysis of the modification of the polarization state of incident polarized light due to the interaction with the sample to be examined, which can be described by the Mueller matrix. In our previous work, it was confirmed that PIT can investigate optical information and microstructures of glioma and non-glioma tissues from clinical treatment based on backward scattering 3 × 3 Mueller matrix polarization imaging experimental setup, and the polarization properties of the glioma and non-glioma brain tissues have been characterized and reported ( Liu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 72%
“…The polarization imaging technique obtains the target's intrinsic properties by acquiring the degree of linear polarization (DoLP) image and the angle of polarization (AoP) image. As an advanced technology, it can not only obtain the polarization information of the target, but also provide the characteristics of light intensity distribution in two-dimensional space, which has a wide range of potential applications in many fields such as target detection [2,3], communication [4], underwater detection [5], and medical imaging [6].…”
Section: Introductionmentioning
confidence: 99%